A Survey on Using Biometrics for Cloud Security - Ruth Ramya, K; N.V.Saikrishna, D; Sravya Nandini, T; Tanmai Gayatri, R (International Journal of Engineering and Technology, 2018)
Cloud computing the most emerging data storage and processing technology. Today many organizations are using cloud-based data storage because of their complex data management. Even though cloud is attracting many users towards using it but there is a requirement of security concerns to be taken care of because cloud is untrusted, the data which individual stores on cloud will be transparent to cloud administrator also which may be confidential. So, while using cloud security is the primary concern. In this paper, we proposed a scheme to encrypt cloud data using user attribute-based encryption. Which is a public key crypto technique in which key will be based on the attributes of user. The attributes we used are biometrics of user who is going to upload the data.Â Â